Media Sosial Sebagai Sumber Pemahaman Politik Pemilih Pemula di Kota Makassar - Ekawati, Dian (LP2M IAIN Palopo, 2021)
Abstract[English]This paper aims to show how the social media became as an important learning space for first-time voter to get their political understanding. In addition, this paper also wants to showed the implications that may arise from that. This is important due to political understanding is an important thing that will shape the political behavior tendencies of first-time voter when they will came to use their political rights in general elections. This paper is based on the results of a qualitative research conducted in Makassar City in 2020. The research was conducted on the first-time voter segment, which is students from several high schools on how social media can be as the important source of information for their political understanding where more than their parents or school. At the end, this paper shows the role of social media for the formation of political understanding of first-time voter in placing themselves properly in a democratic system.Abstrak[Indonesia]Tulisan ini bertujuan untuk menunjukkan bagiamana media sosial menjadi salah satu ruang belajar penting bagi pemilih pemula dalam mendapatkan pemahaman politiknya. Selain itu tulisan ini juga menunjukkan implikasi yang mungkin timbul dari proses tersebut. Hal ini penting mengingat pemahaman politik merupakan hal yang penting yang nantinya akan membentuk kecenderungan perilaku politik pemilih pemula ketika nantinya akan menggunakan hak politiknya dalam pemilihan umum. Tulisan ini didasarkan pada hasil penelitian kualitatif yang dilakukan di Kota Makassar pada tahun 2020. Penelitian dilakukan terhadap segmen pemilih pemula yang merupakan siswa dari bebrapa sekolah menegah atas dan sederajat tentang bagaimana media sosial dapat menjadi sumber informasi bagi pemahaman politiknya. Pada akhirnya tulisan ini menunjukkan peran media sosial bagi pembentukan pemahaman politik pemilih pemula dalam menempatkan diri secara tepat dalam sistem demokrasi.